Parent and Child’s Negative Emotions During COVID-19: The Moderating Role of Parental Attachment Style - Liang, Ziqin; Delvecchio, Elisa; Cheng, Yucong; Mazzeschi, Claudia (Frontiers in Psychology, 2021)
Since February 2020, the coronavirus disease 2019 (COVID-19) has appeared and spread rapidly in Italy. With the health emergency and the social isolation, parents spend more time with their children, and they might have experienced greater distress. Attachment style is considered as an effective emotion regulation strategy in parent-child relationship. However, few empirical studies have addressed this issue. Based on attachment theory, this study aimed to find parental attachment style as a candidate to moderate the relation between parents’ negative emotions and their perceptions of children’ s negative emotions related to COVID-19. Parents (Mage=42.55±6.56, 88.2% female) of 838 Italian children and adolescents aged 3 to 18 participated in an online survey. Results showed that parents with fearful attachment style had significantly higher negative emotions when facing COVID-19 than those with other attachment styles. Moreover, parents with dismissing attachment style perceived fewer negative emotions in their children than parents with fearful and preoccupied styles. At last, higher parents’ negative emotions were associated with greater perception of children’s negative emotions only in parents classified as secure and fearful. These findings suggest that parents with dismissing and fearful attachment styles and their children may be at higher risk during the COVID-19 pandemic and they should be given a long-term attention.